1998
DOI: 10.1901/jaba.1998.31-165
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Pica Through Multiple Analyses of Its Reinforcing Functions

Abstract: We conducted functional analyses of the pica of 3 participants. The pica of 1 participant appeared to be maintained by automatic reinforcement; that of the other 2 participants appeared to be multiply controlled by social and automatic reinforcement. Subsequent preference and treatment analyses were used to identify stimuli that would complete with the automatic function of pica for the 3 participants. These analyses also identified the specific aspect of oral stimulation that served as automatic reinforcement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
196
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 195 publications
(201 citation statements)
references
References 28 publications
(32 reference statements)
4
196
1
Order By: Relevance
“…However, results of the competing stimulus assessment in this investigation and in the Piazza et al (1998) study suggest that this approach to identifying competing stimuli provides information not available with other preference assessments. Perhaps the best example of this is the results obtained for Sally in Phase 2.…”
Section: Discussionmentioning
confidence: 57%
See 4 more Smart Citations
“…However, results of the competing stimulus assessment in this investigation and in the Piazza et al (1998) study suggest that this approach to identifying competing stimuli provides information not available with other preference assessments. Perhaps the best example of this is the results obtained for Sally in Phase 2.…”
Section: Discussionmentioning
confidence: 57%
“…In fact, for all of the participants, there were stimuli that appeared to be similar in terms of item interaction (i.e., how much they were preferred) but were different in terms of how well they competed with the reinforcer for destructive behavior (i.e., how well they substituted for attention). Participants in the study by Piazza et al (1998) showed similar patterns when a competing stimulus assessment was used to identify stimuli that competed with pica. Moreover, in a previous investigation we showed that a competing stimulus assessment accurately identified which stimuli would and would not compete with destructive behavior reinforced by attention (Fisher et al, 2000).…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations